Character Strengths as “Values in Action”: Linking Character Strengths With Values Theory – An Exploratory Study of the Case of Gratitude and Self-Transcendence - Lavy, Shiri; Benish-Weisman, Maya (Frontiers in Psychology, 2021)
Character strengths are widely studied positive traits, considered to be “values in action,” reflecting morally valued virtues. They are hypothesized to serve as pathways to the manifestation of values in life, for the benefit of individuals and societies. However, there is surprisingly limited theoretical writing and empirical research on the expected links of character strengths with specific values (e.g., as defined by Schwartz, 1992) or on character strengths as the pathway for behavioral and social manifestations of these values. In this paper, we delineate theoretical links between the two theories and outline their implications. We then provide an initial empirical examination of a specific character strength – gratitude, as a pathway from Schwartz’s self-transcendence values (self-reported) to prosocial behavior and peer acceptance (rated by peers), in two samples of adolescents (9th grade and 11th grade). The findings indicated that most pathways were significant, providing initial support for the theoretical model. However, in one of the samples, the indirect path from self-transcendence values to prosocial behavior was only marginally significant. Taken together, the findings point to the need for further research on the role of character strengths in creating a pathway from values to various social outcomes.